Keeping Capital Flowing : The Role of the IMF - Bordo, Michael (IMF Working Papers; Working Paper ;, 2004)
In this paper, we examine the IMF's role in maintaining the access of emerging market economies to international capital markets. We find evidence that both macroeconomic aggregates and capital flows improve following the adoption of an IMF-supported program, although they may initially deteriorate somewhat. Consistent with theoretical predictions and earlier empirical findings, we find that IMF-supported programs are most successful in improving capital flows to countries with bad, but not very bad fundamentals. In such countries, IMF-supported programs are also associated with improvements in the fundamentals themselves.